Os Brachyura semiterrestres Crustacea, Decapoda de Ilha Comprida, SP., Brasil - Santos, S.; Souza, P. M.; Goes, P.; Pegorer, C. M. (Inst Tecnologia Parana, 1994)
This work aims to analyse the faunistic composition of ''Ilha Comprida, SP, Brasil, in relation to semiterrestrial crabs. The collects were done during one year. The animals were handy sampled, and the colleting area comprised from Cananeia proximities to Icapara bar, towards north, including beaches, sand banks and mangroves. After each sample the animals were identified. The results obtained were similar those presented for other estuarine regions in São Paulo north coast. With reference to the species from Parana coast, we have got 2 species more. The crabs recorded are distributed in 3 Decapod families: Grapsidae, Ocypodidae and Xanthidae.
The semiterrestrial Brachyura (Crustacea, Decapoda) from Ilha Comprida, SP, Brazil
Keywords: SEMITERRESTRIAL-CRABS; ILHA-COMPRIDA; BRAZIL